Spatial Distribution of Phlebotomine Sand Fly Species (Diptera: Psychodidae) in Qom Province, Central Iran. Issue 1 (28th September 2016) - Saghafipour, Abedin; Vatandoost, Hassan; Zahraei-Ramazani, Ali Reza; Yaghoobi-Ershadi, Mohammad Reza; Rassi, Yavar; Shirzadi, Mohammad Reza; Akhavan, Amir Ahmad
Abstract : Zoonotic cutaneous leishmaniasis (ZCL) is transmitted to humans by phlebotomine sand fly bites. ZCL is a major health problem in Iran, where basic knowledge gaps about sand fly species diversity persist in some ZCL-endemic areas. This paper describes the richness and spatial distribution of sand fly species, collected with sticky traps, in Qom province, a ZCL-endemic area in central Iran, where sand fly fauna has been poorly studied. Collected species were mapped on urban and rural digital maps based on a scale of 1/50, 000. All analyses were undertaken with rural- and urban-level precision, i.e., rural and urban levels were our basic units of analysis. After identifying the sand flies, high-risk foci were determined. For spatial analysis of vector species population, the entomological sampling sites were geo-referenced using GPS. Arc GIS 9.3 software was used to determine the foci with leishmaniasis vector species. Following the analyses, two genera ( Phlebotomus and Sergentomyia ) and 14 species were identified. Based on the mapping and sand fly dispersion analysis, the rural districts were categorized into three groups—infection reported, without infection, and no report. Based on Geographical Information System analyses, Kahak and Markazi districts were identified as high-risk foci with leishmaniasis vector species. These findings can act as a help guide to direct active control measures to the identified high-risk foci and, eventually, lead to reduction in incidence of the disease.